Local Political Power in The Legislation Process - Pawane, Ahmad Rizali; Wijaya, Mohammad Safrul; Ilham, Ilham (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2023)
The democratic system adopted by Indonesia gives a central role to political parties as the main instrument in realizing a democratic state life. This research aims to reveal the political forces that often occur in the legislative process of making regulations in Indonesia. Using a qualitative-descriptive interpretive method and a phenomenological approach, this research explores the political forces involved in legislative making by the executive and legislature. The results show that in regulation-making, there is a power gap between the executive and the legislature. The political power of the executive tends to be dominant because they are the highest power holder. It cannot be denied that there are interests of actors in it who seek to maintain and expand their power. The formation of legal products involves the influence of political power through political processes in state institutions that have authority and power. In addition, this research reveals the political dynamics that occur in the legislative process, where the interaction between the executive and the legislature is a crucial factor. This political process includes negotiations, compromises, and competing interests between the various parties involved. Thus, regulation-making is not only the result of technical considerations and community needs, but also influenced by the dynamics of political power at the local level.